The role of patient care workers in private hospitals in the Cape Metropole, South Africa - Louise A. Aylward; Talitha Crowley; Ethelwynn L. Stellenberg (AOSIS, 2017)
Background: Nursing managers have to meet expectations of patients despite economic pressures, an increasing burden of disease and nursing shortages. Shifting health care-related tasks to lower categories of staff, including non-nursing support staff, has become one solution to address this dilemma. Patient care workers are a specific group of non-nursing support staff working in South African hospitals. Although patient care workers have been used for several years and their numbers are increasing, there are controversial opinions about the role of patient care workers, ranging from praise for their contribution towards patient care to serious concerns about the impact of their role on patient safety. Objective: The study objective was to explore and describe the role of patient care workers in private hospitals. Methods: A qualitative, descriptive design was applied to explore the role of patient care workers. Purposive sampling was used to select unit managers, nurses and patient care workers from medical and surgical wards of three private hospitals. Fifteen semi-structured interviews were conducted and transcribed verbatim. The researcher applied interpretative data analysis to move from the participants' descriptions of their experiences to a synthesis of all participants' descriptions. Results: Patient care workers are involved in direct patient care and spend much time with patients, often not working under direct supervision of registered nurses despite limited training and lack of regulation. Their contribution, however, is valued by nurses. Conclusion: Patient care workers are well-integrated into the patient care team and are mostly seen as nurses. Yet, there are concerns about their evolving role despite their limited training and the lack of direct supervision. Regulating the work of patient care workers is recommended.